Anticancer active trifluoromethylated fused triazinones are safe for early-life stages of zebrafish (Danio rerio) and reveal a proapoptotic action - Małgorzata Sztanke; Jolanta Rzymowska; Krzysztof Sztanke (Taylor & Francis Group, 2021)
The main purpose of this investigation was to evaluate the effect of anticancer active compounds (I-VIII) on zebrafish development in order to select the safest molecules. Larval mortality, embryo hatchability and malformations were end-points used to assess the acute toxicity among embryos and larvae from compounds-/pemetrexed-treated and control groups. LC50 and MNLC (maximal non-lethal concentration) were determined. Lipophilicity-dependent structure-toxicity relationships were established. The results clearly indicated that the majority of test molecules are safe for zebrafish individuals and simultaneously are less toxic than an anticancer agent - pemetrexed. The subsequent aim of this study was to elucidate the molecular mechanism of antiproliferative activity of the most selective compounds. Substantially increased activation of caspase-6 and -8 in cancerous cell lines confirmed the proapoptotic action of molecules examined. Considering the safety for zebrafish individuals, the title compounds as inducers of apoptosis are promising drug candidates in the preclinical phase of drug development.